Association between the guardians' educational levels and unintentional injuries in children aged 6-18 in Shenzhen, China - Yu Xie; Xiaoxuan Yu; Xinyin Wu; Wenyan Zhang; Ziling Feng; Fang Xiao; Xiao Deng; Wenjie Dai; Shaojuan Zhao (BMC, 2024)
Abstract Background Unintentional injuries is the leading cause of death in children aged 6-18 in China. Previous studies on the association between the guardians' educational levels and unintentional injuries in children have been inconclusive, and it remains unclear among the Chinese population. Therefore, this study aimed to identify the association between guardians' educational levels and unintentional injuries in children aged 6-18 in Shenzhen, China. Methods This cross-sectional study enrolled 9,903 children aged 6-18 in Shenzhen in 2020 using a multistage cluster sampling method. Information on the children and guardians were collected, and unintentional injuries in the past year was examined by using two nested questions. Logistic regression analyses were used to test the association between the guardians' educational levels and unintentional injuries in children aged 6-18, and the crude odds ratios (ORs) and adjusted ORs with 95% confidence intervals (95% CI) were calculated. Results 275 of the 9,903 children reported experiencing at least one unintentional injuries in the past year, and the weighted incidence of unintentional injuries was 6.3% (95% CI: 5.8-6.8%) in children aged 6-18 in Shenzhen, China. The incidence of unintentional injuries differed significantly in the guardians' education levels (P < 0.05). After adjustment for the children's variables, multiple binary logistic regression analysis showed that compared to children whose guardians' educational levels were low, children whose guardians' educational levels were high (adjusted OR = 0.57, 95% CI: 0.37-0.87) and medium (adjusted OR = 0.56, 95% CI: 0.39-0.81) had a lower odds of unintentional injuries. Similar results were also observed when further adjustment for both the children's and guardians' variables. Conclusion The overall incidence of unintentional injuries in children aged 6-18 in Shenzhen was low, and it was associated with the guardians' educational levels. Children whose guardians' educational levels were low should be given special concern to prevent unintentional injuries, and it is suggested to reduce the incidence of unintentional injuries in children by improving the guardians' educational levels.